2009
DOI: 10.3844/ajassp.2009.1868.1875
|View full text |Cite
|
Sign up to set email alerts
|

Camel’s Milk Alleviates Oxidative Stress and Lipid Peroxidation Induced by Chronic Aluminum Chloride Exposure in Rat’s Testes

Abstract: Problem statement: The present study was carried out to examine the effectiveness of Camel's milk in alleviating aluminum chloride (AlCl 3 )-induced oxidative stress and lipid peroxidation in rat testes. Approach: White albino male rats (230-250 g) were divided into three groups of 10 rats: A control group, treated with normal saline and two experimental groups, the AlCl 3 treated group and the Camel's milk-AlCl 3 treated group. The first experimental group, the AlCl 3 treated group, received 0.5 mg kg −1 of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…The activities of AST, ALT, ALP and LDH in serum were increased after toxicant administration. These findings are well correlated with those of Abdel Aziz and Zabut (2011) and Al-Hashem (2009). It is of interest to mention that in animals treated with toxicants, the serum levels of these enzymes elevated after liver damage, and thus alterations in liver function, because of increased membrane permeability or due to liver cell necrosis and cytosol leakage into the serum (Ozer et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The activities of AST, ALT, ALP and LDH in serum were increased after toxicant administration. These findings are well correlated with those of Abdel Aziz and Zabut (2011) and Al-Hashem (2009). It is of interest to mention that in animals treated with toxicants, the serum levels of these enzymes elevated after liver damage, and thus alterations in liver function, because of increased membrane permeability or due to liver cell necrosis and cytosol leakage into the serum (Ozer et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…Four groups of rats each of 8 rats were used; they were treated as follows: Control group: Untreated rats, IGE group: Rats received orally γ-irradiated ginseng powder (400 mg kg -1 body wt daily) dissolved in water during the experiment which lasted for six weeks (Turan et al, 2010). AL group: Rats received orally by gavages 1 ml of a solution containing 0.5 mg kg -1 body wt of ALCL 3 in H 2 O per day for six weeks (Al-Hashem, 2009) and IGE + AL group: Rats received IGE + ALCL 3 as described for group 2 and 3.…”
Section: Irradiation Processmentioning
confidence: 99%
“…It has been reported that camel's milk contain high levels of vitamins C (three times that of cow milk and one-and-ahalf times that of human milk), A, B 2 , E and very rich in potassium, iron, magnesium and other trace elements (Pozzilli et al, 2000;Gast et al, 1969;Al-Hashem, 2009). In addition, Gast et al (1969) claim that the value of camel's milk is to be found in the high concentrations of volatile acids, especially, linoleum acid and the polyunsaturated.…”
Section: Discussionmentioning
confidence: 99%
“…Camel's milk also could be used to cure other diseases, such as cardiovascular diseases (Agrawal et al, 2009(Agrawal et al, , 2011Al-Hashem, 2009). It was found that camel's milk reduces the level of blood from fibrinogen in rats with diabetes, indicating the presence of preventive effects of camel's milk in cardiovascular diseases.…”
Section: Other Benefits Of Camel's Milkmentioning
confidence: 99%
“…It was found that camel's milk reduces the level of blood from fibrinogen in rats with diabetes, indicating the presence of preventive effects of camel's milk in cardiovascular diseases. In addition to the mentioned ability to prevent complications of diabetes affecting the cardiovascular system (Agrawal et al, 2009(Agrawal et al, , 2011Al-Hashem, 2009;Gader and Alhaider, 2016). Camel's milk is a good source of protein, calcium, phosphorus, vitamin C, and niacin (Zibaee, 2015).…”
Section: Other Benefits Of Camel's Milkmentioning
confidence: 99%